Α2δ-1–Bound N-Methyl-D-aspartate Receptors Mediate Morphine-induced Hyperalgesia and Analgesic Tolerance by Potentiating Glutamatergic Input in Rodents. (May 2019) - Deng, Meichun; Chen, Shao-Rui; Chen, Hong; Pan, Hui-Lin
Editor's Perspective: What We Already Know about This Topic: Presynaptic N -methyl-D-aspartate receptors contribute to opioid tolerance and hyperalgesia as well as neuropathic pain The α2δ-1 protein subunit enhances presynaptic N -methyl-D-aspartate receptor activity What This Article Tells Us That Is New: Using mouse and rat models, it was demonstrated that α2δ-1 is essential for the increase in presynaptic N -methyl-D-aspartate receptor activity seen during chronic morphine exposure Inhibiting α2δ-1 activity using gabapentin or genetically deleting the gene coding for α2δ-1 results in diminished opioid tolerance and hyperalgesia Background: Chronic use of μ-opioid receptor agonists paradoxically causes both hyperalgesia and the loss of analgesic efficacy. Opioid treatment increases presynaptic N -methyl-D-aspartate receptor activity to potentiate nociceptive input to spinal dorsal horn neurons. However, the mechanism responsible for this opioid-induced activation of presynaptic N -methyl-D-aspartate receptors remains unclear. α2δ-1, formerly known as a calcium channel subunit, interacts with N -methyl-D-aspartate receptors and is primarily expressed at presynaptic terminals. This study tested the hypothesis that α2δ-1–bound N -methyl-D-aspartate receptors contribute to presynaptic N -methyl-D-aspartate receptor hyperactivity associated with opioid-induced hyperalgesia and analgesic tolerance. Methods: Rats (5 mg/kg) and wild-type and α2δ-1–knockout mice (10 mg/kg) were treated intraperitoneally with morphine twice/day for 8 consecutive days, and nociceptive thresholds were examined. Presynaptic N -methyl-D-aspartate receptor activity was recorded in spinal cord slices. Coimmunoprecipitation was performed to examine protein–protein interactions. Results: Chronic morphine treatment in rats increased α2δ-1 protein amounts in the dorsal root ganglion and spinal cord. Chronic morphine exposure also increased the physical interaction between α2δ-1 and N -methyl-D-aspartate receptors by 1.5 ± 0.3 fold (means ± SD, P = 0.009, n = 6) and the prevalence of α2δ-1–bound N -methyl-D-aspartate receptors at spinal cord synapses. Inhibiting α2δ-1 with gabapentin or genetic knockout of α2δ-1 abolished the increase in presynaptic N -methyl-D-aspartate receptor activity in the spinal dorsal horn induced by morphine treatment. Furthermore, uncoupling the α2δ-1– N -methyl-D-aspartate receptor interaction with an α2δ-1 C terminus–interfering peptide fully reversed morphine-induced tonic activation of N -methyl-D-aspartate receptors at the central terminal of primary afferents. Finally, intraperitoneal injection of gabapentin or intrathecal injection of an α2δ-1 C terminus–interfering peptide or α2δ-1 genetic knockout abolished the mechanical and thermal hyperalgesia induced by chronic morphine exposure and largely preserved morphine's analgesic effect during 8 days of morphine treatment. Conclusions: α2δ-1–Bound N -methyl-D-aspartate receptors contribute to opioid-induced hyperalgesia and tolerance by augmenting presynaptic N -methyl-D-aspartate receptor expression and activity at the spinal cord level. Abstract : Using mouse and rat models, it was demonstrated that α2δ-1 is essential for the increase in presynaptic N -methyl-d-aspartate receptor activity seen during chronic morphine exposure. Inhibiting α2δ-1 activity using gabapentin or genetically deleting the gene coding for α2δ-1 results in diminished opioid tolerance and hyperalgesia.